Considerations and approaches to expansion of solid organ transplant pharmacist services. Issue 11 (1st September 2021) - Doligalski, Christina Teeter; Anger, Lyndsey Bowman; Dick, Travis; Feist, Ashley; Harris, Matt; Masters, Brian; Pilch, Nicole; Quan, David; Sparkes, Tracy; Suarez, Tricia; Yakubu, Idris
Abstract: Solid organ transplantation is a lifesaving procedure for thousands of people with irreversible end organ diseases. A multidisciplinary approach with inclusion of a pharmacist in the care of transplant recipients is highly desired and may necessitate the addition of transplant pharmacy resources to existing teams to meet these growing needs. By understanding and leveraging the current landscape of leadership priorities, gathering the data to help define the value of pharmacy services, and compiling a formal proposal, one can systematically approach expansion of clinical pharmacy services. This manuscript seeks to provide a framework that can be utilized by pharmacy and transplant administrators, transplant pharmacists, and advocates for transplant pharmacy services for the purpose of evaluating, proposing, and successfully expanding the number of transplant pharmacist resources, including example job descriptions, return on investment examples, and key publications demonstrating the benefit of transplant and pharmacy services.